2015
DOI: 10.1371/journal.pone.0142689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Modification on Telomerase Gene Expression in Hypertensive Patients: A Pilot Trial of Stress Reduction and Health Education Programs in African Americans

Abstract: BackgroundAfrican Americans suffer from disproportionately high rates of hypertension and cardiovascular disease. Psychosocial stress, lifestyle and telomere dysfunction contribute to the pathogenesis of hypertension and cardiovascular disease. This study evaluated effects of stress reduction and lifestyle modification on blood pressure, telomerase gene expression and lifestyle factors in African Americans.MethodsForty-eight African American men and women with stage I hypertension who participated in a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 71 publications
3
58
1
1
Order By: Relevance
“…This may be due to the improvement of their knowledge following the instruction regarding diet and stress management. This result was also showed by Duraiman et al [28] who reported that relaxation increases the secretion of endorphin hormone and decreases the secretion of adrenalin hormone. It improves blood circulation and decreases anxiety and stress by creating a positive attitude and improving brain function.…”
Section: 4supporting
confidence: 82%
See 1 more Smart Citation
“…This may be due to the improvement of their knowledge following the instruction regarding diet and stress management. This result was also showed by Duraiman et al [28] who reported that relaxation increases the secretion of endorphin hormone and decreases the secretion of adrenalin hormone. It improves blood circulation and decreases anxiety and stress by creating a positive attitude and improving brain function.…”
Section: 4supporting
confidence: 82%
“…The symptoms of depression and lifestyle also improved among participants after the implementation of the nursing intervention. A similar result was supported by Duraimani et al, [28] who observed reduced sodium and protein consumption among all subjects; while a large number of the health education group revealed reduced intake of calories, carbohydrates, and fats than the stress reduction group.…”
Section: The Risk Factors Of Hypertension and Dyslipidemiasupporting
confidence: 79%
“…These results are consistent with previous studies of TM indicating that this practice may produce physiological changes associated with stress in the absence of changes in self-reported psychological variables. 36,37 Fifth, no record of compliance for home TM practice was collected. However, the record of meeting attendance was significantly higher in the TM (80.6%) as compared with HE (50.2%) group (P=.001).…”
Section: Stress Reduction For Preventing Lvh -Schneider Et Almentioning
confidence: 99%
“…Of note, the Atherosclerosis Risk in Communities (ARIC) study has shown that TERT polymorphisms are associated with increased risk of incident coronary heart disease, incident ischemic stroke, and mortality in African-Americans participants (79). Stress reduction and lifestyle modification in this same high risk population increase telomerase gene expression and produce an associated reduction in blood pressure (BP), suggesting that enhanced telomerase gene expression may either be a biomarker for reduced BP or a mechanism by which stress reduction and lifestyle modification reduces BP (80). Moreover, telomerase deletion increases endothelin ET-1 levels in the plasma suggesting that loss of telomerase may contribute to increased vasoconstriction and hypertension (81).…”
Section: Role Of Telomerase In Of Cardiovascular Diseasementioning
confidence: 99%